The international companion to James Macpherson and The Poems of Ossian - Bär, Gerald (2019)
Recensão de: Moore, Dafydd, ed.- The International Companion to James Macpherson and The Poems of Ossian. International Companions to Scottish Literature. Glasgow: Association for Scottish Literary Studies, 2017. 187 p.